Islamic Education Theory Al-Zarnuji's Perspective in The Book Ta'lim Al-Muta'allim - Mufid Mufid; Abas Mansur Tamam (Pusat Publikasi Nusantara, 2024)
Islamic education is one of the important pillars in Islamic civilization, Islamic education remains interesting and relevant because Islamic education figures have produced works that are very valuable for the development of Islamic education. These works are still relevant and continue to be studied today. One of the scholars who is categorized as an expert in Islamic Education and is considered to have an original and inspiring work is Imam Al-Zarnuji in his work Ta'lim Al-Muta'allim. So the purpose of this study is to analyze the theory of Islamic Education from Al-Zarnuji's perspective in the book Ta'lim Al-Muta'allim. The research method used in the research uses descriptive qualitative methods. Data collection is done through literature study then the collected data is analyzed through three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that Ta'lim al-Muta'allim, which consists of thirteen chapters, emphasizes moral education and basic foundation knowledge in shaping the character and learning achievement of santri. This is relevant to character education in Indonesia. However, there are criticisms which in general from the title and systematics of the discussion are considered to only discuss student manners, not explicitly discussing teacher manners. Therefore, many state that the Ta’lim al-Muta’allim book is more oriented towards the student centered education model